Experimental investigation of the interface bond properties between SHCC and concrete under sulfate attack. (30th August 2019) - Gao, Shuling; Jin, Jiapeng; Hu, Guanhua; Qi, Lin
Highlights: The bonding strength degradation rate of SHCC was slower than concrete. The corrosion resistance coefficient of SHCC remained 60% at 120 corrosion cycles. The interface structure in SHCC can well prevent the invasion of sulfate ions. Abstract: A new class of high-performance fiber reinforced cementitious composite, namely Strain-Hardening Cementitious Composites (SHCC), is characterized by strain-hardening, multiple-cracking and tight crack width. This paper investigates the coupled action of sulfate and wet-dry cycles on the degradation degree of interfacial bonding performance of SHCC/concrete, through slant shear and splitting tensile test coupled with Na2 SO4 wet-dry cycles. The degradation mechanism is investigated with SEM and XRD. The results show that the erosion resistance of SHCC/concrete interface is better than concrete/concrete for a range of cycles from 0 to 120. The strength of SHCC/concrete decreased more slowly than concrete/concrete, and the corrosion resistance coefficient can still reach above 60% even after 120 cycles (no matter in Type A or Type B test). By contrast, the reinforced concrete B and existing concrete A are separated from one another, when the cycles are more than 90 in Type B test. SHCC and existing concrete A was found to form a more compact structure by micromechanical analysis, which reduced calcium vanadium and enhanced the sulfate resistance of structure.